(untitled) (LACCEI, 2024)
In many countries, most organic waste is usually placed in landfills, which generates public concern about the health effects of emissions pollutants. The natural bacterial decomposition of organic waste produces landfill gases, about half of the methane, with the remainder mainly carbon dioxide and minor amounts of other gases. Real-time measurement and modeling of emissions gases in landfills are essential. This work develops a low-cost wireless measurement system using MOS gas sensors (MQ4, MQ5, and MQ9), a 32 bits microcontroller, an XBee module, and HC-12 wireless communications modules. The system can be mounted on an uncrewed aerial vehicle (UAV, drone) or deployed as a wireless sensor network. Experiments have been carried out near a closed landfill, and measurement results show high methane concentrations.